2015
DOI: 10.1016/j.jare.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Why the radiation-attenuated cercarial immunization studies failed to guide the road for an effective schistosomiasis vaccine: A review

Abstract: Graphical abstractSchistosomula- and adult worms-derived antigens induce predominant Th1 immune responses. The radiation-attenuated cercariae vaccine efficacy is dependent on induction of Th1 and Th2 immune responses. Accordingly, schistosomula- and adult worms-derived antigens used for effective vaccination must be combined with Th2 immune responses-inducing cytokines or molecules as adjuvant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 160 publications
(227 reference statements)
0
19
0
1
Order By: Relevance
“…mansoni consistently, and reproducibly elicited highly significant ( P < 0.0001) reduction in worm burden of 70% ±3. The reduction was also highly significant for decrease in worm liver ( P < 0.0001) and small intestine ( P < 0.001) egg counts but only of approximately 50% ( 14 ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…mansoni consistently, and reproducibly elicited highly significant ( P < 0.0001) reduction in worm burden of 70% ±3. The reduction was also highly significant for decrease in worm liver ( P < 0.0001) and small intestine ( P < 0.001) egg counts but only of approximately 50% ( 14 ).…”
Section: Discussionmentioning
confidence: 92%
“…This belief was based on preponderance of interferon-gamma (IFN-γ) released by bronchoalveolar leukocytes, total lung tissue, and lung-draining lymph nodes in radiation-attenuated (RA) cercariae-vaccinated mice ( 11 , 12 ). Lung schistosomula-derived antigens seeping in lung tissues or released from extravasated dying larvae expectedly induce preponderant type 1 immune responses [( 13 , 14 ) and references therein]. Yet, these immune responses might be irrelevant to parasite attrition, as it must be reiterated healthy schistosomes are exclusively intravascular and may not be directly affected by the immune events in lung alveoli, parenchyma, or draining lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since currently available vaccine candidate formulations mediate type 1-biased protective immunity, which is limited or partial at best, it is important to revisit the lessons of the radiation-attenuated (RA) cercarial vaccine ( 9 ). In this respect, a meta-analysis of the experimental studies undertaken with the RA cercarial vaccine in mice (755 observations from a total of 105 articles) was performed by Fukushige et al ( 10 ), who reported that the RA vaccine has the potential to induce protection as high as 78% with a single dose of vaccine.…”
mentioning
confidence: 99%
“…(3) Specific antibodies may access the worm gut lumen and those that escape immediate digestion might be able to neutralize and interfere with enzymes critical for worm feeding and fecundity, but not survival, as these processes by definition impact on juvenile and adult worms not schistosomula migrating in the lung capillaries and liver sinusoids ( 4 ). (4) We are left then with the hunt and chase theory, whereby immune antibodies and cells interact with excreted–secreted parasite products in the vicinity of migrating schistosomula, alarming and activating effector immune cells ( 2 , 9 , 12 ). (5) Eosinophils and basophils would be particularly effective immune cells but need a type 2 immune environment for recruitment and activation ( 2 , 9 , 12 , 13 ).…”
mentioning
confidence: 99%